The effect of a digital game-based learning task on the acquisition of the English Article System. (December 2020) - Kao, Chian-Wen
Abstract: This study investigated whether students' article accuracy could be improved through a digital game which provides a realistic business task in which a player serves as an employer interviewing potential employees and the English article system is employed for communication during conversational turn taking. Research participants were divided into three groups: the digital game-based learning group, the cloze exercise with corrections group, and the cloze exercise group. Three job application letter writing tasks served as pretests, immediate posttests and delayed posttests. The results of the immediate posttests revealed that the cloze exercise with corrections group outperformed the other two groups in terms of English article accuracy (F = 11.915, p = .000). No significant difference was discovered between the digital game-based learning and cloze exercise groups. In the 1-month-delayed posttest, the cloze exercise with corrections group still outperformed the cloze exercise group in terms of English article accuracy (F = 18.460, p = .000). However, the digital game-based learning group, beyond all expectations, significantly outperformed the cloze exercise with corrections group. The digital game that provides focused correction on article errors may be more beneficial to learners than traditional teacher correction.